Basis of the ius puniendi in matters of sanctioning administrative law and its difference with respect to the criminal sphere: A jurisprudential and comparative analysis - Vélez Martínez, Marcelo (Revista de Derecho Público, 2022)
The objective of this work is to analyze the problem that arises between the penalizing administrative law and criminal law, unraveling the underlying foundations that obey the idea of ius puniendi in terms of its legal nature. This may, based on a historical-legal study, what has been understood by national and international doctrine and jurisprudence, considering the concepts of crime and administrative infraction.